[Letter from the Bakery, Confectionary and Tobacco Workers Union to Representative Rich Boucher] (Tufts Archival Research Center, 2007)
Letter from Frank Hurt, International president of the Bakery, Confectionary and Tobacco Workers International Union to representative Rich Boucher regarding the proposed increase in the cigarette excise tax. Claims tax will destroy tobacco industry in Virginia and numerous jobs will be lost.